Some features of the causal links in different cultures - E. A. Dolgova (Vestnik MGIMO-Universiteta)
This article touches upon the problem of the meaning of causation and its role in forming and functioning of linguistic and cultural map of the world. The author comes to the conclusion, that in a process of consideration of problems concerned with methods of causal connection organization some specific national features of different nations' relations to some categories, like cause and effect are exposed. The knowledge of the reasons of different events and phenomena occurring in a society assists in a much more successful realization of multicultural communication.